Effect Of Tofu Liquid Waste Mix With EM4 Fermented Palm Oil Liquid Waste On The Growth Of Chlorella sp. On Gambut Water Media - Muhammad Fitra; Budijono Budijono; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractThe tofu industry and palm oil mills produce a lot of residual production of high organic matter. With the addition of EM4, the residual production can be accelerated decomposition into a nutrient-rich material so that it can be utilized for the growth of Chlorella sp. This study aims to determine the benefits of a mixture of tofu liquid waste with palm oil mill liquid waste for the growth of Chlorella sp. on peat water media conducted in March - September 2019 at the FPK Alga Research Center Laboratory of the University of Riau. Tofu liquid waste samples were taken in Pekanbaru City and the Palm Oil Mill at PTPN V Tandun and peat water from the Kuala Terusan River in Pelalawan Regency. The number of treatments in this study were 5 treatments with 3 replications consisting of P0 (0%), P1 (25%), P2 (50%), P3 (75%), and P4 (100%), where the value of% in each of these treatments is the result of a mixture of liquid waste between the two industries in an operational volume of 1500 ml. Each treatment was added with 25 ml of Chlorella sp. with a culture period of 10 days. The parameter measured is abundance. The results showed the best media at P2 (50%) with an initial abundance of 0.987 x 106 cells / ml to 7.850 x 106 cells / ml on the 7th day. It was concluded that the mixture of tofu liquid waste with palm oil mill liquid waste can be used as nutrition for the growth of Chlorella sp. Keyword:Microalgae, Organic matter, Nutrition, EM4, Abundance.